Application of a free preputial tube graft coupled with urethral plate urethroplasty combined with a Buck's fascia integral covering for the single-stage repair of severe hypospadias - Zhou, Wei; Li, Changpei; Xia, Fan; Zhang, Qi; Chen, Yanxing (Frontiers in Surgery, 2023)
Summary: Objective: To assess the outcome of free preputial tube graft coupled with urethral plate urethroplasty combined with Buck's fascia integral-covering(BFIC) for single-stage repair of severe hypospadias in children. Materials and Methods: A retrospective study was performed on 40 children with hypospadias who were treated in our hospital from December 2017 to February 2022. Inclusion criteria: 1. Proximal hypospadias, or penile curvature over 30 degrees after degloving of the penis; 2. underwent hypospadias surgery for the first time. Free preputial tube graft coupled with urethral plate urethroplasty combined with Buck's fascia integral-covering was performed, and all patients were followed up for more than 6 months. Results: After foreskin-degloveing,the urethral orifice was retracted to the perineum and scrotum in 20 cases, penoscrotal in 8 cases, and penile in 12 cases. Single-stage repair was achieved without complications in 34 patients (85%).The remaining 6 patients with postoperative complications , urethrocutaneous fistula occurred in 5 cases and glans dehiscence with urethrocutaneous fistula in 1 case. No urethral diverticulum occurred in all cases. With one exception,a neo-meatus with a vertically oriented slit-like appearance was achieved at the tip of the glans in the remaining 39 cases. Conclusion: Single-stage operation with free preputial tube graft coupled with urethral plate urethroplasty combined with Buck's fascia integral-covering in the treatment of severe hypospadias achieves favorable functional and cosmetic outcomes .